Evaluation of Mediastinal Masses through Computed Tomography (CT) - Aniket M. Zope; Snehil Kumar; Uday M. Zende; Amol A. Gautam (Medical Research and Its Applications Vol. 10, 2024)
Mediastinal masses are indicative of a broad range of disease states, some of which may be entirely asymptomatic or exhibit symptoms and indicators of intrathoracic pathology. A chest X-ray can identify a mediastinal mass, but a CT scan is required to characterize the mass in further detail. Patients from our hospital who were suspected to have a mediastinal mass either on clinical examination or on the basis of an abnormal chest radiograph were included in the study. The patients were subjected to a thorough history and clinical examination. The advantages of CT such as better spatial resolutions, shorter imaging time, less expensive and its availability made CT a better imaging technique. Co-existing lung abnormalities and calcifications within the lesions are better appreciated on CT. CT examination of the patient was done using a Philips Ingenuity 128-slice CT scanner. Our study included a total of 50 cases, 31 males and 19 females. The anterior mediastinum is the most commonly involved compartment (n=27, 42.2%), followed by the middle (n=23, 35.9%) and posterior mediastinum (n=14, 21.8%). Thymic masses (n=7, 46.6%), Aneurysms (n=6, 54.5%) and Nerve sheath tumors (n=4, 33.3%) are the most common masses to have isolated compartmental involvement of anterior, middle and posterior mediastinum respectively. The majority of the mediastinal masses are well defined (n=36, 72%), with soft tissue (n=34, 68%) attenuation on plain CT, showing heterogeneous enhancement (n=22, 44%) on the administration of intravenous contrast. Computed tomography is an important modality in the evaluation of mediastinal masses for their exact localization, analyzing their morphology and arriving at a provisional diagnosis for optimal patient management. Most of the mediastinal masses are well defined, with soft tissue attenuation on the plain study, showing heterogenous enhancement in contrast study. Thus, CT with an overall accuracy of 94% is an important imaging modality in the evaluation of a mediastinal mass.